2005
DOI: 10.1007/s10750-004-4868-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem response to changes in water level of Lake Ontario marshes: lessons from the restoration of Cootes Paradise Marsh

Abstract: A general understanding of how aquatic vegetation responds to water-level fluctuations is needed to guide restoration of Great Lakes coastal wetlands because inter-annual and seasonal variations often confound effects of costly remedial actions. In 1997, common carp (Cyprinus carpio) was removed from Cootes Paradise Marsh (L. Ontario) to reduce sediment resuspension and bioturbation, and thus regenerate marsh plants that had declined dramatically since the 1930s. Data from 1934 to 1993 were re-assembled from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…It is, therefore, recommended that further study be conducted to see whether this change in water volume reaching receiving waters over time will impact on the ecological environment as the studies presented by Chow-Fraser [2] and Papastergiadou et al [3] have shown that even slight changes over time can make an impact on the ecological environment. As this study only presents hypothetical scenarios of the application of WSUD to a catchment, further validation of the study in functional catchments with varying ranges of WSUD implemented should be considered.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, recommended that further study be conducted to see whether this change in water volume reaching receiving waters over time will impact on the ecological environment as the studies presented by Chow-Fraser [2] and Papastergiadou et al [3] have shown that even slight changes over time can make an impact on the ecological environment. As this study only presents hypothetical scenarios of the application of WSUD to a catchment, further validation of the study in functional catchments with varying ranges of WSUD implemented should be considered.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…This has the potential to adversely impact the ecosystem. Undesirable ecological and environmental impacts of reductions in water flow have already been established [2,3]. However, the potential adverse impacts of WSUD implementations have yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…had their greatest frequencies in older restorations, particularly in 2017. This variation and decline could be due to grazing from waterfowl (Lauridsen et al 1993), water level fluctuations (Chow-Fraser 2005), changes in light conditions (Bini et al 1999), temperature (Minc 1997, Smith andMoelyowati 1998), or changes in nutrient inputs (Lougheed et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In an effort to remedy the degradation of shallow lakes, several restoration projects have focused on implementing this wet-dry cycle as a management tool (Chow-Fraser 2005, Giesthardt et al 2013). Many of these projects focus on maintaining conditions that favor abundant vegetation, particularly emergent vegetation and submersed aquatic plants, and may result in a shift to a clear water state , Chow-Fraser 2005, Søndergaard et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation